Nutritional Response of Sweet Potato Genotypes on Saline Inceptisol - and D. Burman, K. Laxminarayana (Journal of the Indian Society of Soil Science, 2014)
A field experiment was conducted for two consecutive rabi seasons during 2009-2011 to find out the suitable genotypes for salinity stress and the effect of graded doses of NPK and organic manure for sustainable production, proximate composition and nutrient uptake of sweet potato (Ipomoea batatas L.) on saline Inceptisol of West Bengal. Among the genotypes, Samrat was found superior in respect of tuber yield (19.6 t ha-1) followed by CIP-440127 (18.3 t ha-1), whereas significantly highest vine yield was observed for Pusa Safed (23.9 t ha-1) that was similar to Samrat (22.6 t ha-1). Application of 75 N - 22 P – 63 K (kg ha-1) recorded highest tuber yield (18.3 t ha-1) with all varieties. Significantly highest starch and dry matter contents (22.8 and 30.9%, respectively) were recorded in Kishan, while those parameters were highest (21.8 and 30.3%, respectively) with the application of 100% NPK. Significantly highest total uptake of N, P and K was observed in Samrat. Incorporation of organic manure i.e. 5 t FYM ha-1 alone has shown almost equivalent yield response and quality over that of 75% NPK. The genotypes Samrat, CIP-440127 and Pusa Safed were relatively tolerant to salinity stress (10-20 dS m-1), and application of 100% NPK produced more yield of sweet potato.